Inter-Laboratory Study on Measuring the Surface Charge of Electrically Polarized Hydroxyapatite - Ubele-Kalnina Darta; Nakamura Miho; Gross Karlis Agris (MDPI, 2025)
Surface charges on implants improve integration into bone and so require a clear protocol for achieving a surface charge and comparable results from different laboratories. This study sintered hydroxyapatite (HAp) at one laboratory to remove the influence of the microstructure on surface charge and then polarized/depolarized the pellets at two different laboratories (in Tokyo and Riga). Surface charges on HAp pellets induced by electric polarization at 400 °C in a 5 kV/cm DC electric field were measured by the thermally stimulated depolarization current (TSDC) method as 6–9 µC/cm2. The surface charge results were comparable between laboratories and also agreed with previously documented values. Recommendations describe conditions for polarization and depolarization to generate a surface charge and repeatedly achieve a comparable outcome. A visual display of the polarization mechanisms and the contribution to surface charge point to further aspects that need further development.